Analisis Kemiskinan di Kota Besar Pulau Jawa - Widhian Hardiyanti; Andi Kartika; Sartika Wulandari (Universitas Medan Area, 2021)
This study aims to examine and analyze the effect of Literacy Rate (LR) and Gross Regional Domestic Product (GRDP) on Poverty in the Big Cities of Java Island from 2015 to 2019. The population in this study is all people in the poor category in Indonesia. The samples in this study were people who were categorized as poor in the big cities of Java, namely the Special Capital Region of Jakarta, Bandung, Semarang, Surabaya, DIY, and Banten. Data were analyzed using panel data regression (pooled data) with a total sample of 30 data. The data processing tools in this study use Ms. Excel and Eviews no 9. The panel data regression model options include Estimating Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM). Model selection using Chow Test and Hausmant Test. The results of the two tests recommend researchers use the output of the Fixed Effects Model for hypothesis testing. Results show that the Literacy Rate (LR) has a negative and significant effect on poverty in Big Cities in Java. GDRP doesn’t affect poverty in Big Cities in Java